ANALISIS KETERAMPILAN SOSIAL SISWA DALAM PEMBELAJARAN EKONOMI KELAS XI IPS DI SMA SANTO FRANSISKUS ASISI - Gabriela Vera Lara Rejeki; Endang Purwaningsih; Husni Syahrudin (Universitas Tanjungpura, 2020)
AbstractThis research aimed to determine social skills of students in learning Economics class XI IPS SMA Santo Fransiskus Asisi. This research was based on the finding of a problem when researcher made observations about students' social skills in learning Economics. The research method used was the type of qualitative research and in form of descriptive research. Sources of data in this research were students of class XI IPS totaling 37 people and the Economics teacher. Data collection was obtained through observation guidelines and interview guidelines, and then analyzed using data reduction, data presentation, and drawing conclusions/verification on students' social skills based on a comparison of percentages and predicates, then checking the validity of the data using triangulation techniques. Researcher conducted the research by observing 3 times and interviewing 2 days. The results showed that social skills of students had already taken place in the process of Economics learning class XI IPS SMA Fransiskus Asisi. These skills included Social Presentation skills can be categorized quite well by having a percentage of 67%, Social Scanning Skills can be categorized quite well by having a percentage of 64%, and Social Flexibility skills can be quite well categorized by having a percentage of 63%.Keywords: Economics Learning, Social Skills, Students of Class XI IPS